Kegiatan Pengabdian Masyarakat dengan Skrining Cemaran Bakteri (E.coli) dan Corynebacterium spp. pada Air Bersih di Duri Kosambi - Donatila Mano S.; Alexander Halim Santoso; Bryan Anna Wijaya; Fiona Valencia Setiawan; Gracienne Gracienne; Edwin Destra; Farell Christian Gunaidi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Clean water is a fundamental necessity for public health, as water contamination can lead to various health problems, such as gastrointestinal infections, skin diseases, and other health issues. Screening for water contamination by Escherichia coli bacteria and Corynebacterium spp. is essential to ensure water quality remains safe. This community service activity was conducted in the Duri Kosambi area, focusing on education and water quality testing. The program included planning educational sessions on the risks of water contamination, implementing screenings using colony-forming unit (CFU) parameters to detect Escherichia coli and Corynebacterium spp., and evaluating results to provide preventive recommendations. The findings revealed variations in contamination levels across locations, with some meeting cleanliness standards, while others, such as B04, showed extreme contamination. This activity highlights the importance of community education, regular water quality monitoring, and water treatment to prevent health risks. Collaboration among communities, governments, and health organizations is crucial to maintaining sustainable access to high-quality clean water.